If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 6 + -2r = 7r + -10 Reorder the terms: 6 + -2r + 5t = 7r + -10 Reorder the terms: 6 + -2r + 5t = -10 + 7r Solving 6 + -2r + 5t = -10 + 7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7r' to each side of the equation. 6 + -2r + -7r + 5t = -10 + 7r + -7r Combine like terms: -2r + -7r = -9r 6 + -9r + 5t = -10 + 7r + -7r Combine like terms: 7r + -7r = 0 6 + -9r + 5t = -10 + 0 6 + -9r + 5t = -10 Add '-6' to each side of the equation. 6 + -9r + -6 + 5t = -10 + -6 Reorder the terms: 6 + -6 + -9r + 5t = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -9r + 5t = -10 + -6 -9r + 5t = -10 + -6 Combine like terms: -10 + -6 = -16 -9r + 5t = -16 Add '-5t' to each side of the equation. -9r + 5t + -5t = -16 + -5t Combine like terms: 5t + -5t = 0 -9r + 0 = -16 + -5t -9r = -16 + -5t Divide each side by '-9'. r = 1.777777778 + 0.5555555556t Simplifying r = 1.777777778 + 0.5555555556t
| y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x | | 70x^3+112x-1=0 | | 108=-6(x-8)-4x | | 7n=50+24 | | Y-3=-(x-5) | | (5x+y)+(2x+6y)= | | 2(x+9)=26 | | 3*8x=1.5e^2x | | x^4+0.5x^3-6x^2+5=0 | | g-(-7)=13 | | 33=6a+2 | | 20p-(7+2p)= | | z^2+(4+2i)z+(2-3i)=0 | | 39-15y=-31-5y | | 21y^14-7y^4=0 | | 2y-4x=-3-2x+y | | 8x-5=63 | | (3.2+1)-(0.6*7)= | | Logx(256)=2 | | 5+2y=(-1) | | -14x+2y=-2 | | -3(2a-3)=3(a-6) | | h+4=2h-19 | | z=3*x-y | | y=0.95x | | 9.2-x=7.3 | | -7x+y=-1 | | 3x-11=x-5 | | -3(2x-3)=3(x-6) |